TERPENE PRODUCTS PURIFICATION - Rizqia Ayudina, Dara
Turpentine is an oil that can be obtained from the distillation process of sap derived from the stems of Pinus merkusii as a top product. The constituent compounds of turpentine oil are ?-pinene, ?-pinene, limonene, 3-karen, and camphene. The compound has a much higher utility and value than the turpentine oil itself. However, the process of separating each component is quite difficult because of its high boiling point. It is easily damaged and decomposed at high operating temperatures will cause a decrease in quality. Therefore, to maintain its quality, vacuum distillation is carried out by lowering the operating pressure with a pump so that the boiling point of the components can be decreased. This research focuses on refining -pinene because this compound is the main component of terpene oil with the highest composition compared to other components. The objective of this research is to analyze the optimum operating conditions in the purification process of terpene products by partial vacuum distillation. From these optimum conditions, the highest composition and profit of the terpene product will be obtained. The variations of the operating conditions are operating pressure and reflux ratio. The varied operating conditions include operating pressure and reflux ratio. The operating pressure is varied at 320, 350, 470, and 530 mmHg, while the reflux ratio to distillate (R/D) is varied at 2, 3, and 4. This research consisted of four stages: analysis of turpentine oil feed with GC-MS, fractionation or separation process of ?-pinene using a batch vacuum distillation column, analysis of the fractionation results using GC-FID, and analysis of bottom product with GC-MS. This research showed that the higher vacuum and R/D ratio, the purity of ?-pinene in product will be higher. Considering the level of purity and economic advantage, the most optimum operating conditions are 368,788 mmHg of pressure and 3,7 of R/D ratio, which obtaining yield with value 40%-vol from feed with a 93,13% purity of ?-pinene and 4,5621 USD/2 L of net profit.